Pengaruh Insentif Terhadap Kinerja Karyawan dengan Kepuaan Kerja sebagai Variabel Mediasi (Studi Pada Karyawan Perhotelan Bintang 3 Di Provinsi Lampung) - Antonius Panji Utomo; Fitra Dharma; Widya Rizki Eka Putri (Goodwood Publishing, 2022)
This study aims to analyze the effect of incentives on employee performance with job satisfaction as a mediating variable. This analysis is focused on employees so that employee performance is more optimal and improved. There are 3 variables used in this study, namely: incentives as the independent variable, employee performance as the dependent variable and job satisfaction as a mediating variable. The approach used in this study is a quantitative approach with data collection using a questionnaire distributed to all hotel employees. This research was conducted in all 3-star hotels in Lampung Province. The theory used in this study is the two-factor theory. This two-factor theory separates two sets of satisfaction and dissatisfaction. The sampling technique in this research is to use purposive sampling based on certain considerations. Respondents used as many as 302 employees, using the calculation of the Slovin formula. While the analytical method used in this research is multiple linear regression analysis. The program used in analyzing the data for this research is the Statistical Package for Social Sciences (SPSS) Ver.21.00.